Findings From the 2021 Organizational Value of Nursing Professional Development Practice Study, Part 2: Relationships Between Nursing Professional Development Staffing and Organizational Outcomes. Issue 5 (7th September 2022) - Harper, Mary G.; Maloney, Patsy; Aucoin, Julia; MacDonald, Ryan
Abstract : A 2015 study exploring the relationship between nursing professional development (NPD) staffing and organizational outcomes was replicated in 2021. The background, including literature review, methods, and descriptive statistics, were presented in Part 1 of this report. Part 2 explores the relationships between NPD staffing and organizational outcomes. Evidence suggests that higher levels of NPD staffing are associated with many positive nursing and patient outcomes and provide financial benefit to the organization.